Unveiling the secrets of marine—derived fucoidan for bone tissue engineering—A review - V. K., Anupama Devi; Udduttula, Anjaneyulu; Jaiswal, Amit Kumar (Frontiers in Bioengineering and Biotechnology, 2023)
Biomedical uses for natural polysaccharides of marine origin are growing in popularity. The most prevalent polysaccharides, including alginates, agar, agarose and carrageenan, are found in seaweeds. One among these is fucoidan, which is a sulfated polysaccharide derived from brown algae. Compared to many of the biomaterials of marine origin currently in research, it is more broadly accessible and less expensive. This polysaccharide comes from the same family of brown algae from which alginate is extracted, but has garnered less research compared to it. Although it was the subject of research beginning in the 1910s, not much has been done on it since then. Few researchers have focused on its potential for biomedical applications; nevertheless, a thorough knowledge of the molecular mechanisms behind its diverse features is still lacking. This review provides a quick outline of its history, sources, and organization. The characteristics of this potential biomaterial have also been explored, with a thorough analysis concentrating on its use in bone tissue engineering. With the preclinical research completed up to this point, the fucoidan research status globally has also been examined. Therefore, the study might be utilized as a comprehensive manual to understand in depth the research status of fucoidan, particularly for applications related to bone tissue engineering.